CYTOPROTECTNE EFFECT OF ALLOPURINOL ON ETHANOL INDUCED GASTRIC MUCOSAL DAMAGE IN RATS - Nadir YÖNETÇİ; A. Ömer ÖZÜTEMİZ; Tijen TANYALÇIN; Fatma KUTAY; Yücel BATUR (Turkish Journal of Gastroenterology, 2020)
-